Translation Strategy of Proper Name - M. Agus Suriadi; Ni’ mah Nurul Ihsani (Insaniyat : Journal of Islam and Humanities, 2019)
Massive discussion has been done related to the translation strategy, including the proper name. This study discussed the types of a proper name and the translation strategy of a proper name in an English-Indonesian Novel Harry Potter and The Chamber of Secret. The data will be presented qualitatively by using Peter Newmark and Lincoln Fernandes theories. Six data are frequently typed into addressing name, four are typed as a geographical place, and one as an object name. Moreover, the most strategies used to engage the equivalence effect are copy strategy with seven data, rendition strategy with three data, and re-creation strategy with one datum. Therefore, the copy strategy can be a solution to deliver proper names into TL because it preserves the proper name and introduces the foreign name of foreign culture to the target language and target culture. Moreover, if a proper name has its equivalence meaning in TL, it might be translated by rendition strategy.